The Effect of Taxation Knowledge and Tax Sanctions to Taxpayer Compliance - Abdul Halim Rachmat, Radhi (International Journal of Psychosocial Rehabilitation, 2020)
This study is to know how the influence of taxation knowledge and tax penalty on taxpayer obedience on the entrepreneur’s personal taxpayer in the Pratama Tax Service Office Bogor. The factors that are tested in this study are taxation knowledge and tax penalty as independent variables, while taxpayer obedience is a dependent variable. The sample that is used in this study is 100 respondents by using the probability sampling method with the Slovin formula. While the analysis method that is used on this study is multiple linear regression analysis on the significance level of 5% by using the SPSS application. The result of this study shows that taxation knowledge and tax penalties have a significant influence on taxpayer obedience in the Pratama Tax Service Office Bogor. While the amount of influence taxation knowledge and tax penalty on giving an influence contribution to taxpayer obedience is 80%.